THE EFFECT OF ORGANISATIONAL CULTURE, POSITION PROMOTION AND SERVICE QUALITY ON EMPLOYEE PERFORMANCE OF THE POPULATION AND CIVIL REGISTRATION OFFICE OF KERINCI REGENCY - Yass Andria; Yonet Efendi; Donal Candra; First Fardian (Jurnal Ekonomi, 2023)
This research aims to determine the influence of Organizational Culture, Position Promotion and Service Quality on the Performance of Population and Civil Registration Service Employees in Kerinci Regency. This research uses qualitative and quantitative research methods, where the sampling technique uses a total sampling technique, with a total sample of 31 employees of the Kerinci Regency Population and Civil Registration Service. The analysis technique is multiple regression analysis. The results of this research are both partial and simultaneous Organizational Culture, Position Promotion and Service Quality on Employee Performance of the Kerinci Regency Population and Civil Registration Service The purpose of this study was to determine whether there is an influence.